Politics and Trade Policy: An Empirical Investigation - Theo Eicher; Thomas Osang (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper we examine the empirical relevance of three prominent endogenous protection models. Is protection for sale, or do altruistic policy makers worry about political support? We find strong evidence that protection is indeed for sale. The important new result is, however, that not only the existence of lobbies matters, but also the relative size of the sectoral pro and anti protection contributions. All variables of both the Influence Driven (Grossman and Helpman, 1994) and the Tariff Function (Findlay and Wellisz, 1982) models are significant at the one percent level. Novel is our application of a single, unified theoretical framework to take strict interpretations of the three theoretical models to the data. We thus extend the previous tests of the Influence Driven approach by comparing its performance to well specified alternatives. Using J tests to compare the power of the models directly, we find significant misspecification in the Political Support Function approach. We cannot reject the null hypothesis of correct specification of the Influence Driven model and find evidence of some misspecification in the Tariff Function model.
Keywords: D72; F13; P16; 330; Endogenous protection; lobbying; political economy of tariffs